AN ANALYSIS OF INFLECTIONAL AND DERIVATIONAL AFFIXES OF THE STUDENTS’ TEXT - Furqon Edi Wibowo; Endang Rismawati (IKIP Siliwangi, 2022)
Morphology is needed in writing. Most of students have low understanding on it. Therefore, this study was to analyze types of inflectional and derivational affixes at the eighth grade students’ writing skill of recount text at SMP N 2 Wonosari in the academic year of 2021/2022 and to describe the students’ problems in using affixes. The data were collected by documentation, interview and questionnaire. The researcher used Miles and Huberman’s theory to analyze data. The trustworthiness of the data used theory triangulation. The result showed there were 7 types of inflectional affixes –ed, -s, irregular form, -‘s, -en, -er and suppletive plural. There were 6 types of derivational affixes Verb to Noun, Adjective to Adverb, Noun to Adjective, Adjective to Noun, Verb to Adjective, and Noun to Noun (-er, -or, -ion, -ment, -er, -ly, -y, -al, -able, -ous, -ic, -ful, -ry, -ness, -dom, and –ship). The problems happened to the students in using affixes such as the students had difficulties in distinguish free morpheme and bound morpheme, the students were still confused to determine the affix and root, the students felt difficult on the words that consisted of derivational affixes. The affixes could also change the sound and spelling. Keywords: Morphology, Inflectional affixes, Derivational Affixes, Wrriting, Recount Text